Colección Estéticas Contemporáneas Universidad Pontificia Bolivariana - Cardona Restrepo, Porfirio; Santamaría Velasco, Freddy (Estudios de Filosofía, 2018)
The birth of the collection "Contemporary Aesthetics" is based on the following question: When thinking today about the role of aesthetics, do we, in turn, rethink the function of philosophy? Can you talk about a pragmatist aesthetic? What do artistic expressions communicate, and how do they impact other social practices? These questions raise research regarding some of the new challenges of aesthetics, challenges that have been rigorously addressed by the American philosopher Richard Shusterman (2000). Shusterman and Danto understand that language is eminently communication and that with this same performative language, you can do things with words (following Austin and Searle). Shusterman (2000) proposes that aesthetic considerations are crucial in determining how we choose to lead our lives and what we consider a good life to be. Considerations that recall Wittgenstein’s dictum according to which ethics and aesthetics are one (Shusterman, 2000, p. 237). From these ideas, the function of philosophy, in relation to the artistic experience, becomes vitally important since by rethinking art from a pragmatist aesthetic, the very function of philosophy is rethought.